Organic field effect transistors comprising copolymers synthesized without structure-directing moieties with enhanced carrier mobility - Swain, Gitanjali; Javaregowda, Bharathkumar H.; Dambhare, Neha V.; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2023)
Conjugated materials are synthesized by C-C bond formation reactions. Trimethyltin and boronic acid are two widely used structure-directing moieties. While using the ethynyl moiety as a part of the monomer, additional structure-directing moieties are not needed. However, ethynylene will be part of the conjugated material. Often, the polymers with an ethynylene moiety negatively impact the polymers' properties. However, the ethynylene moiety could minimize the dihedral angle if the monomer has steric functionalities. For example, BODIPY is an attractive monomer due to its high molar extinction coefficient, partial quinoidal character, and high quantum yield. However, materials based on BODIPY exhibited poor charge carrier mobility due to steric hindrance generated by four methyl groups. Herein, we copolymerize BODIPY with ethynylene comprising i-indigo and thieno-i-indigo. The copolymer with thieno-i-indigo showed increased molecular weight and significantly reduced band gap compared to the copolymer with i-indigo. The copolymer with i-indigo showed immeasurably low hole transport mobility. On the other hand, the copolymer with thieno-i-indigo exhibited 0.003 cm2V(-1) s(-1). These measurements were made using field effect transistors. We also measured the charge carrier mobility using the space charge-limited current method. Both copolymers exhibited a mobility of 10(-3) cm(2) V-1 s(-1).
Keywords: acetylene linkage; BODIPY; field effect transistor; iso-indigo; Sonogashira coupling; thienoisoindigo